Increasing Use of Less-Invasive Hemodynamic Monitoring in 3 Specialty Surgical Intensive Care Units: A 5-Year Experience at a Tertiary Medical Center. (January 2015) - Kirton, Orlando C.; Calabrese, Rebecca C.; Staff, Ilene
Introduction: Less-invasive hemodynamic monitoring (eg, esophageal doppler monitoring [EDM] and arterial pressure contour analysis, FloTrac) is increasingly used as an alternative to pulmonary artery catheters (PACs) in critically ill intensive care unit (ICU). Hypothesis: The decrease in use of PACs is not associated with increased mortality. Methods: Five-year retrospective review of 1894 hemodynamically monitored patients admitted to 3 surgical ICUs in a university-affiliate, tertiary care urban hospital. Data included the number of admissions, diagnosis-related group discharge case mix, length of stay, insertion of monitoring devices (PAC, EDM, and FloTrac probes), administered intravenous vasoactive agents (β-predominant agonists—dobutamine, epinephrine, and dopamine; vasopressors—norepinephrine and phenylephrine), and mortality. Data from hospital administrative databases were compiled to create patient characteristic and monitoring variables across a 5-year time period, 2005 to 2009 inclusive. Chi-square for independent proportions, 1-way analysis of variance, and Kruskal-Wallis tests were used; tests for trend were conducted. An α level of .05 was considered significant. Statistical Package for the Social Sciences v14 was used for all statistical testing. Results: There was a significant change in the type of hemodynamic monitors inserted in 2 of the 3 surgical ICUs (in the general surgery and neurointensive care but not in the cardiac ICU) from PACs to less-invasive devices (FloTrac or EDM) during the 5-year study period ( P < .001). There was no change in mortality rate over the time period ( P = .492). There was an overall increase in the proportion of monitored patients who received intravenous vasoactive agents ( P < .001) with a progressive shift from β-agonists to vasopressors ( P < .002). Multivariate analyses indicated that age, case mix, and use of vasoactive agents were all independent predictors of inhospital mortality ( P = .001) but that type of monitoring was not ( P = .638). Conclusions: In a 5-year period, the decreased insertions of PACs were replaced by increased utilization of less-invasive hemodynamic monitoring devices. This change in practice did not adversely impact mortality.